Synergy between the North Sumatra Regional Police and the National Narcotics Agency of North Sumatra Province in Combating the Illicit Trafficking of Narcotics and Illegal Drugs - Theresia Hutasoit; Janpatar Simamora; Ojak Nainggolan (Sultan Agung Notary Law Review, 2026)
In order to combat illicit narcotics trafficking in the Medan area—the provincial capital and the region with the highest level of narcotics circulation in North Sumatra—this study will examine the elements that help and those that hurt the cooperation between the North Sumatra Regional Police (Polda North Sumatra) and the National Narcotics Agency of North Sumatra Province (BNNP North Sumatra). This qualitative study confirmed the existence of operational synergy in the drug prevention, eradication, abuse, and illicit trafficking programs, as well as in the disclosure of large drug networks in combination, the existence of clear legal fees regarding cooperation between institutions, and a common vision.